Risk Factors of Hernia in Hadramout Yemen: A Case Control Study - Aram, Fahmi Omer (Author) : Banafa, Nawal Saeed (مجلة الأندلس للعلوم الاجتماعية والتطبيقية, 2023)
Risk Factors of Hernia in Hadramout Yemen: A Case Control Study